Evaluasi dan impact assessment pelatihan sekolah lapang pengendalian hama terpadu (SL-PHT) tanaman jagung melalui pengenalan dan aplikasi pestisida nabati di Kabupaten Purbalingga - Lili Adam Yuliandri; Rachmi Alnido2 (Fakultas Pertanian Universitas Majalengka, 2023)
The Sri Lestari farmer group in Karangbanjar Village, Bojongsari District, Purbalingga Regency works on the cultivation of food crops such as corn and rice, some of them working on horticultural crops. The use of chemical fertilizers and chemical pesticides carried out from year to year is quite worrying with the increasing dose of use of Chemical Fertilizers as well as environmentally unfriendly chemicals that are concerned will damage the natural ecosystems. The implementation of integrated pest management field schools (SL-IPM) corn farm efforts are expected to be able to impact the level of application of integrated pesticide control through the identification and application of plant pesticides on the Sri Lestari farmer group. The aim of the study was to analyze the impact of the SL-IPM implementation on the level of application of integrated pest control and the socioeconomic impacts of members of the Sri Lestari group. This research was conducted in May 2023. The number of respondents was 35 people using the census technique. Data is analyzed quantitatively. The observed variables are characteristics, pre-test and post-test, and socio-economic impact assessment of members of the farm group. The results of that there was an improvement in understanding, changes in attitudes, skills, knowledge and behavior in the good category (when an increase in respondent understanding of the training material was more than 30% of all pre-test and post-test questions). The number of members of the peasant group who applied the FS-IPM principle of corn crops was 62.86% with an increase in corn productivity of 50.91%.